2014
DOI: 10.1016/j.expthermflusci.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of carbon nanotubes water based nanofluids as coolants

Abstract: International audienceThe thermo-physical properties of water-based nanofluids containing carbon nanotubes, stabilized by SDBS as surfactant, are experimentally studied. The effect of low nanoparticle volume fraction, ranging from 0.0055% to 0.278%, on density, thermal conductivity and viscosity of nanofluids is investigated for temperature range of 20°C to 40°C. Enhancement in density, thermal conductivity and viscosity of nanofluids with volume fraction in nanotubes is shown in comparison to base fluids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(106 citation statements)
references
References 40 publications
(67 reference statements)
4
95
0
Order By: Relevance
“…The enhancement in thermal conductivity of water was achieved when the amount of dispersed carbon nanotubes was increased [18,19]. It was also reported that 5% volume fraction of TiO2 nanoparticles and 7.5% of volume fraction of CuO enhanced thermal conductivity of water by 33% and 32%, respectively [20,21], whereas 5% volume of ZnO enhanced thermal conductivity of water by 12% [22].…”
Section: Introductionmentioning
confidence: 85%
“…The enhancement in thermal conductivity of water was achieved when the amount of dispersed carbon nanotubes was increased [18,19]. It was also reported that 5% volume fraction of TiO2 nanoparticles and 7.5% of volume fraction of CuO enhanced thermal conductivity of water by 33% and 32%, respectively [20,21], whereas 5% volume of ZnO enhanced thermal conductivity of water by 12% [22].…”
Section: Introductionmentioning
confidence: 85%
“…Low nanoparticle volume fraction, ranging from 0.0055% to 0.278%, showed positive effect on density, thermal conductivity and viscosity of nanofluids for temperature range of 20-40°C. Enhancement in density, thermal conductivity and viscosity of nanofluids with volume fraction in nanotubes was observed in comparison to base fluids [40][41][42].…”
Section: Low Temperature Collectormentioning
confidence: 82%
“…Xiao et al [6] reported that very thin CNT films radiate lurid sound, and therefore prepared thin film CNT megaphones. Halelfadel et al [7] examined the productivity of water-based nanofluid CNTs and deliberated the consequences of stumpy volume fraction nanoparticles in a range from 0.0055% to 0.278% on the physical properties (density, viscosity, thermal conductivity, and specific heat) of nanofluids. Aman et al [8] investigated the influence of magnetohydrodynamics on Poiseuille flow and heat analysis of CNTs with a Casson fluid vertical channel.…”
Section: Introductionmentioning
confidence: 99%
“…The density, specific heat capacity, and rate of thermal conductivities of the nanofluid [7,8] are expressed as:…”
mentioning
confidence: 99%